The epidemiology of neonatal respiratory distress in a tertiary care neonatal Centre Kashmir India - Gaurav; Naik, Suhail Ahmad; Ahmad, Syed Tariq (International Journal of Contemporary Pediatrics, 2023)
Background: Respiratory distress is most common cause of neonatal admission to NICU and has different etiologies with similar clinical presentation. Early diagnosis of specific cause for respiratory distress is very important as different etiologies have different specific treatment and require altogether different ventilatory strategies. Objectives were to study the demographic and etiological profile of neonatal respiratory distress. Method: Hospital based prospective observational study conducted in department of pediatrics, associated hospital of GMC Srinagar. Results: Respiratory distress was more common in males 56.30%, frequency of prematurity was 68% and most common mode of delivery lower section caesarian section (LSCS) 69.10%. Different maternal risk factors associated with adverse outcome premature rupture of membranes (PROM) (37.7%), meconium-stained amniotic fluid (MSAF) (34.60%), maternal hypertension (31.50%), gestational diabetes mellitus (GDM) (26.9%). Common causes for respiratory distress in neonate were transient tachypnea of newborn (TTN) (22.0%), respiratory distress syndrome (RDS) (20%), meconium aspiration syndrome (MAS) (16.90%), sepsis (14%) and perinatal asphyxia (12%). Conclusions: Early diagnosis of specific cause for respiratory distress is very important as different etiologies have different specific treatment and require altogether different ventilatory strategies. The TTN was the most common cause of distress in term newborns, followed by perinatal asphyxia, meconium aspiration, neonatal sepsis, and congenital heart diseases (CHD). Therefore, timely diagnosis and management of these conditions is very imperative to discharge an intact neonate from the NICU.